LocoMMotion: a study of real-life current standards of care in triple-class exposed patients with relapsed/refractory multiple myeloma : 2-year follow-up (final analysis) - Mateos, Maria-Victoria; Weisel, Katja; De Stefano, Valerio; Goldschmidt, Hartmut; Delforge, Michel; Mohty, Mohamad; Dytfeld, Dominik; Angelucci, Emanuele; Vincent, Laure; Perrot, Aurore; Benjamin, Reuben; van de Donk, Niels W. C. J.; et al. (World psychiatry, 2024)
Treatment of relapsed/refractory multiple myeloma (RRMM) is challenging as patients exhaust all available therapies and the disease becomes refractory to standard drug classes. Here we report the final results of LocoMMotion, the first prospective study of real-world clinical practice (RWCP) in triple-class exposed (TCE) patients with RRMM, with a median follow-up of 26.4 months (range, 0.1-35.0). Patients (N  =  248) had received median 4 prior LOT (range, 2-13) at enrollment. 91 unique regimens were used in index LOT. Overall response rate was 31.9% (95% CI, 26.1-38.0), median progression-free survival (PFS) was 4.6 months (95% CI, 3.9-5.6) and median overall survival was 13.8 months (95% CI, 10.8-17.0). 152 patients (61.3%) had subsequent LOTs with 134 unique regimens, of which 78 were used in first subsequent LOT. Median PFS2 (from start of study through first subsequent LOT) was 10.8 months (95% CI, 8.4-13.0). 158 patients died on study, 67.7% due to progressive disease. Additional subgroup analyses and long-term safety summaries are reported. The high number of RWCP treatment regimens utilized and poor clinical outcomes confirm a lack of standardized treatment for TCE patients with RRMM, highlighting the need for new treatments with novel mechanisms.